The environmental impact of goats: uprooting the narrative - Loomis, Cara; Kerven, Carol (Frontiers in Animal Science, 2025)
Every few years, an old story resurfaces in the popular media: goats are especially harmful to the environment because they uproot plants, preventing them from regrowing and thus turning grasslands into deserts. The destructive tendencies of goats in these accounts have “unleashed some of the worst dust storms on record”, overgrazed Mongolia’s “once verdant land”, and prevented entire ecosystems from growing back. However, what evidence exists to demonstrate that goats are uniquely predisposed to uproot grasses and cause untold environmental damage? When we turn to the scientific literature on goat grazing habits, we find that there is a lack of evidence to support the claim that goats dig up plant roots. This leads us to scrutinise the putative role that goats have played in causing overgrazing, ecological decline, and ultimately, desertification. What emerges reverses the widely held view; rather than causing desertification, goats are best equipped to deal with its effects. The physiology of goats makes them particularly well-suited to exploiting marginal ecological zones created through changing climate patterns. The final section calls for a revaluation of goats. Frequently raised by some of the most economically and environmentally marginalised populations across the world, goats offer these communities a degree of food security that is unmatched by other livestock species. What if built into the cost of a cashmere sweater is not environmental decline, but economic support for communities bearing the brunt of shifts in global climate patterns that are out of their control and not of their making?